Model Perjanjian Baku Pada Kontrak Berlangganan Sambungan Telekomunikasi Telepon Selular Pasca Bayar - Elis Herlina; Sri Santi (Fakultas Hukum Universitas Islam Indonesia, 2016)
The contract to subscribe to the telecommunication connection of postpaid cellular phone is a standard contract made by the business actor by almost not giving freedom at all to other parties to do negotiation for the requirements offered. This research is to study: first, is the implementation of standard contract for the subscription contract of telecommunication connection of postpaid cellular phone suitable with the legal principles of the contract? Second, how the model of standard contract in the contract of subscription for the telecommunication connection of the postpaid cellular phone is viewed from the contract laws and Law Number 8 of 1999 on the Consumer Protection? This is a normative-juridical research. The result of the research concluded that first; the subscription contract for the telecommunication connection of postpaid cellular phone theoretically has fulfilled the provisions of the Article 1320 Civil Law on the requirement of the contract legality. Second, the model of the subscription model of telecommunication connection of postpaid cellular phone must provide the clauses in accordance with the Law of Consumer Protection particularly limited with the Provision of Article 18 of Laws of Consumer Protection.